Radioactive characterization of Ar-Rassafeh Badyieh area (Area-2), Syria by using Statistical factor analysis technique - ASFAHANI, Jamal; AL-HENT, Rashad; AISSA, Mosa (Contributions to Geophysics and Geodesy, 2018)
A scored lithological map including nine litho-factor units is established through applying the statistical factor analysis technique (SFAT) to aerial spectrometric data of Area-2 (Al-Rassafeh Area), which includes T.C, eU, eTh, K, eU/eTh, eU/K, and eTh/K. A model of four rotated factors F1, F2, F3, and F4 is adapted for representing 61712 data measured points in Area-2, where 90.3% of total data variance is interpreted. The isolated lithological units related to F1, F2, and F3 are characterized by an eU average of 2.15, 0.99, and 1.57 ppm respectively. Two geological scored pseudo-sections derived from the lithological scored map are established and analyzed in order to show the mutual environmental geological relationships between different lithological isolated units. This scored map will be the base for further geological investigations in Area-2. SFAT has proven its efficacy in the research study Area-2, and allowed the different isolated sectors to be characterized and interpreted geologically and radioactively.